Interpersonal Meaning of Mangupa Towards Dalihan Na Tolu Tapanuli Selatan in Medan - Daulay, Irma Khoirot (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2021)
The recent study analyzed the interpersonal meaning of "mangupa" process to obtain the interpretation of language in its function as an exchange of experience. And the interpersonal meaning of the utterances uttered by Dalihan na tolu of Mora, Kahanggi, and Anak boru, show the form of each position and the meaning. This study is qualitative research, which naturally observed the data and analyzed it based on the interpersonal analysis. This research found that the text in mangupa is dominantly realized in statement form. Statements come from giving, information from the source/speaker. And the second is offering; the offer was realized from giving, goods/services from source/ speaker. Mora, kahanggi and anakboru were giving statement in mangupa process of Angkola's wedding ceremony. In addition, these three participants demonstrate their role while Kahanggi as the moderator of the ceremony, anakboru as the helper who takes responsibility for preparing the things needed at every stage of the ceremony, while mora has the authority to provide guidance, suggestion, permission, and rejection at the ceremony.